2020
DOI: 10.3390/mi11020186
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Microfluidic Device Integrated with Chitosan-Modified Capillaries for Rapid ZIKV Detection

Abstract: The outbreak of Zika virus (ZIKV) has posed a great challenge to public health in recent years. To address the urgent need of ZIKV RNA assays, we integrate the microfluidic chip embedded with chitosan-modified silicon dioxide capillaries, smartphone-based detection unit to be a C3-system for the rapid extraction and detection of ZIKV RNA. The C3-system is characterized by: (1) four chitosan-modified silicon dioxide capillaries integrated in the microfluidic chip for target ZIKV RNA enrichment and “in situ PCR”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…As a result, nucleic acid extraction from saliva is relatively simple and less tedious compared to other body fluids. Several miniaturized systems using saliva as a diagnostic fluid have been developed ( Chen et al, 2010 ; Wand et al, 2018 ; H. Yang et al, 2018 ; Zhu et al, 2020 ). These integrated systems utilized SPE ( Chen et al, 2010 , 2013 ; H. Yang et al, 2018 ), paper-based extraction ( Jiang et al, 2018 ; Seok et al, 2019 ; R. Tang et al, 2017a ), or pH-responsive polymer-based extraction ( Zhu et al, 2020 ) for rapid sample preparation from saliva (also see Table 2 ).…”
Section: Nucleic Acid Extraction From Oral and Nasal Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, nucleic acid extraction from saliva is relatively simple and less tedious compared to other body fluids. Several miniaturized systems using saliva as a diagnostic fluid have been developed ( Chen et al, 2010 ; Wand et al, 2018 ; H. Yang et al, 2018 ; Zhu et al, 2020 ). These integrated systems utilized SPE ( Chen et al, 2010 , 2013 ; H. Yang et al, 2018 ), paper-based extraction ( Jiang et al, 2018 ; Seok et al, 2019 ; R. Tang et al, 2017a ), or pH-responsive polymer-based extraction ( Zhu et al, 2020 ) for rapid sample preparation from saliva (also see Table 2 ).…”
Section: Nucleic Acid Extraction From Oral and Nasal Samplesmentioning
confidence: 99%
“…(f) Schematic illustration of a Zika virus detection chip embedded with chitosan-modified capillaries to capture viral RNA from saliva (reproduced with permission from Ref. ( Zhu et al, 2020 ), © MDPI 2020). …”
Section: Nucleic Acid Extraction From Oral and Nasal Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some challenges such as weak reproducibility, instability and lack of multiplexing capability are yet to be addressed to translate the technologies into practical applications.Several research articles have reported the development of chip-, paper-, and nanomaterial-based POC devices for Zika virus detection, sperm quality assessment, and opto-acoustic sensing. Zhu et al [3] developed "C 3 -system", a sample-to-answer microfluidic device for POC detection of Zika virus RNA. This device consists of chitosan-modified silicon dioxide capillaries, a pneumatic unit, a heating unit and a smartphone.…”
mentioning
confidence: 99%